Lexical Semantic Errors in Undergraduate Students' Academic Writing - Letsoela, Puleng Makholu; Matlosa, Litsepiso (FOSTER: Journal of English Language Teaching, 2022)
In language teaching and learning, the correct use of vocabulary in the target language is as important as the language's grammar. This study investigates lexical semantic errors in the academic writing of 4th-year undergraduate students at the National University of Lesotho. Using the random sampling method, ten Action Research reports were selected. Errors were identified and analyzed using Hemchua and Schmitt's (2006) classification. Findings in the study indicate that errors resulting from the confusion of sense relations were most frequent, followed by errors in collocation and translation errors. The study recommends that teaching communication skills courses offered at the year 1 level should include explicit vocabulary teaching to minimize semantic errors, which, as is argued, result in incomprehensible texts.